Pengaruh Strategi Promosi terhadap Volume Penjualan Produk Hijabi Regional Tasikmalaya - Sopa Nurjanah; Eman Sulaiman; Bambang Sumardi (Yayasan Literasi Sains Indonesia, 2024)
This research is to determine the effect of promotional strategies (X) on the sales volume (Y) of hijabi products in the Tasikmalaya region. In increasing sales, companies are required to carry out more effective marketing activities in finding solutions and strategies to be able to continue to survive in the very tight competition in the business world. This research uses descriptive quantitative methods, data sources are primary and secondary data with data collection techniques using questionnaires, interviews, and observation. The population in this study were costumers who purchased hijabi products in the Tasikmalaya region in one month, namely 594 consumers. The sample taken was 86 respondents. The sampling technique uses a probability sampling technique with an error rate of 10% using the slovin formula. The data processing technique uses the SPSS verson 27 program. The research results show that promotional strategy (X) has an effect on sales volume (Y) based on hypothesis testing, the thaung valuue is 10.644 > ttabel 1,667 and is confirmed by sig. equal to 0.001 < 0.05, meaning that promotional strategies have an effecct on sales volume. In the coefficient of determination (R2) test of 0.574 it means that the promotional strategy variable influences sales volume by 57.4%, while the remaining 42.6% is influenced by variables not examined in this research.